Enhancing physical characteristics of thermotropic nematic liquid crystals by dispersing in various nanoparticles and their potential applications - Rastogi A.; Mishra A.; Pandey F.P.; Manohar R.; Parmar A.S. (My University, 2025)
Herein, we have summarized the doping of thermotropic nematic liquid crystals (LCs) with different nanoparticles (NPs) and its consequences on dielectric, optical, and electro-optical properties. The challenging task is to improve the physical properties of nematic LCs for its applications in nanotechnology, which include sophisticated and highly advanced modern displays, tunable lenses, sensors, etc. The negative effects that affect the overall performance of LCs devices are image sticking problem, image flickering, and slow response time which is mainly affected by ions and alignments. The trapping of charged ionic impurities and suppression of screening effect through NPs in LC medium produces strong electric field and van der Waal forces linked with the LC molecules and the alignment layers. The electric field controls the orientation of LC molecules and thus transforms its physical behavior. In this article, we have summarized and discussed the physical properties of thermotropic nematic LCs with the dispersion of NPs. These thermotropic LCs require improvement in their properties for the better functioning of LC products. A decade of enthusiastic research has designed the lane to the suspension of NPs in LC matrix for resolving the issues on nanotechnology. NPs (guest) that are embedded in LCs (hosts) influence its material parameters. The present article focuses on the review of published articles which report various types of NPs (metal oxide NPs, carbon-based NPs, semiconducting NPs, ferroelectric (FE) such as BaTiO3, magnetic NPs, and metallic NPs) as dopants and its sound realization on the physical properties of thermotropic nematic LCs. The topological defects and the effect of dispersion of colloidal particles in nematic LCs have been discussed. The decrease in the anchoring energy with decreasing radius of particles has been revealed. This review considers the significant role of NP self-assembly in LC medium which depends on its shape, size, and surface chemistry that affect the orientation order of LC molecules. From the application point of view, this review provides the literature support where the mixing of LCs and NPs solves the technological problems. The explanation on the improvement in the performance/material parameters is well supported by the experimental literature study reported in this review. © 2022, Qatar University and Springer Nature Switzerland AG.